Comparison of assembly process and co-occurrence pattern between planktonic and benthic microbial communities in the Bohai Sea - Liu, Jinmei; Wang, Xiaolei; Liu, Jiao; Liu, Xiaoyue; Zhang, Xiao-Hua; Liu, Jiwen (Frontiers in Microbiology, 2022)
Unraveling the mechanisms structuring microbial community is a central goal in microbial ecology, but detailed understanding of how community assembly processes relate to living habitats is still lacking. Here, via 16S rRNA gene amplicon sequencing, we investigated the assembly process of microbial communities in different habitats (water verse sediment, free-living [FL] verse particle-associated [PA]) and their impacts on the inter taxa association patterns in the coastal Bohai Sea, China. The results showed clear differences in the composition and diversity of microbial communities among habitats, with greater dissimilarities between water column and sediment than between FL and PA communities. The microbial community assembly was dominated by dispersal limitation, ecological drift and homogeneous selection, but their relative importance varied in different habitats. The planktonic communities were mainly shaped by dispersal limitation and ecological drift, whereas homogeneous selection played a more important role in structuring the benthic communities. Furthermore, the assembly mechanisms differed between FL and PA communities, especially in the bottom water with a greater effect of ecological drift and dispersal limitation on the FL and PA fractions, respectively. Linking assembly process to co-occurrence pattern showed that the relative contribution of deterministic processes (mainly homogeneous selection) increased under closer co-occurrence relationships. By contrast, stochastic processes exerted a higher effect when there were less inter taxa connections. Overall, our findings demonstrate contrasting ecological processes underpinning microbial community distribution in different habitats including different lifestyles, which indicate complex microbial dynamic patterns in coastal systems with high anthropogenic perturbations.